DISEMINASI MEDIA PROMOSI KAMPUNG WISATA BALUWARTI GUNA MENINGKATKAN BRAND IDENTITY DESTINASI PARIWISATA BUDAYA KOTA SURAKARTA - Nanang Wijayanto; Tomi Agfianto; Deria Adi Wijaya (Jurnal Inovasi Penelitian, 2022)
This activity carried out an inventory of the right Baluwarti tourist attractions to be used as content in making promotional media, the right arrangement of interesting tourism activities followed by making promotional media and managing promotional media for one year and seeing the response of tourists visiting Baluwarti Tourism Village based on promotional media references. which has been published. Baluwarti Tourism Village with an attraction that offers, namely nuances that can be enjoyed by tourists, feel the atmosphere of living together with the culture of the palace, learn and process to be involved in the activities of the local community, tourists do not just see but are also involved in the cultural joints of the people in it Tourists can feel and fully enjoy the socio-cultural activities in the Baluwarti Tourism Village. From these activities the objectives to be achieved are: 1.Creating promotional media to promote community-based tourism and the culture contained therein. 2. Provide benefits to the community, to improve brand identity. 3. Can preserve culture and to avoid reduction and degradation of culture. In addition to these goals, there are also several benefits to be achieved, namely: 1. Play an active role in introducing and promoting tourism so that cultural preservation can be maintained as a national identity. 2. Excite the arts and culture to support the development of the Baluwarti Tourism Village as a Tourism Village. 3. To be able to maintain the nobility of culture, especially the sacred values ​​of the palace, do not become profane passed down from generation to generation, so that harmony, welfare, and safety can be maintained. 4. Strengthening and using the right promotional media in order to increase Brand Identity will be able to increase the value of benefits for the people of the Baluwarti Tourism Village by increasing tourism activities, it will increase welfare for the community.